Kinesiophobia, catastrophizing, and the duration of immobilization: A prospective study on factors associated with shoulder disability following wrist-hand injuries - Cantero-Téllez, Raquel; Rider, John; Cruz Gambero, Leire; Villafañe, Jorge Hugo; Valdes, Kristin (Elsevier, 2025)
Background Shoulder pain is a major musculoskeletal problem after wrist-hand immobilization. There is limited evidence regarding the relationship of kinesiophobia or pain catastrophizing with shoulder pain and disability after wrist-hand injury. Purpose To explore associations between kinesiophobia and pain catastrophizing with ipsilateral persistent shoulder disability in patients with wrist-hand injury after 6 months. Study Design Prospective study. Methods Participants aged ≥18 years referred to hand therapy after wrist-hand injury requiring wrist-hand immobilization were recruited and completed the Numeric Pain Scale, Shoulder Pain and Disability Index, Pain Catastrophizing Scale (PCS), and Tampa scale for kinesiophobia (TSK) at baseline, after an immobilization period, and after 6 months. Results A total of 107 patients were included in the study. Scaphoid fractures were found in 49 (45.8%) of patients, and 58 (54.2%) had distal radius fractures. For each week of increased time spent in immobilization, the Shoulder Pain and Disability Index score increased by 10.2 points, 95% confidence interval (CI) [6.76, 13.57], with higher levels of immobilization being associated with increased shoulder pain and disability. The baseline TSK score was 17.4 and 11.2 at follow-up. The PCS score was initially 14.8 and decreased to 9.3 at follow-up. The addition of TSK and PCS to the predictive model led to a statistically significant increase in R2 of 0.163, F(2,100) = 47.471, p < 0.001. Conclusions The duration of wrist immobilization following an injury may play a crucial role in the level of shoulder disability experienced at the 6-month mark post-injury. This shoulder disability may be influenced by factors such as fear of movement.
Keywords: Manos - Lesiones y heridas; Hombros - Enfermedades; Dolor; Rehabilitación; Immobilization; Pain; Rehabilitation; Shoulder; Wrist